siRNA-mediated knockdown of FoxP3 promotes the ratio of T-helper 1 (Th1) to Th2 in chronic hepatitis B patients - Li XIAOLIANG; Yu YONGSHENG; Tang ZHENGHAO; Zang GUOQING (Turkish Journal of Gastroenterology, 2019)
-